Revisiting the theological underpinnings of the Kairos Document and its relevance for the church in Zimbabwe - Mujinga, Martin (HTS teologiese studies, 2025)
The publication of the Kairos Document in 1985 marked a significant shift in the political, theological and social history of South Africa. The document challenged inequalities, oppression, the apartheid system and structural injustices. The underpinnings of the Kairos Document influenced churches outside South Africa to challenge their governments on the socioeconomic and political status of their nations. This article aims to revisit the theological underpinnings of the Kairos Document, to assess how its presuppositions are relevant to the church in Zimbabwe. Using the pastoral letter of the Zimbabwe Catholic Bishops’ Conference, ‘The March Is Not Ended’, as a case study, the article resonates with the bishops’ stance that institutionalised corruption, lawlessness, unresolved past atrocities and human rights abuses are multiple layers dividing the country. The article argues that, whereas the Kairos Document challenged the South African church during apartheid, the Catholic bishops’ pastoral letter serves as a prophetic voice to the Zimbabwean government that ill-treats its citizens in an independent country. Upon reading the two documents, the article employs a qualitative research methodology to argue that every generation faces its challenges, and there is never a time when the church’s prophetic voice should be silent. The article concludes by arguing that the underpinnings of the Kairos Document remain alive as long as politicians use and abuse the Bible for their selfish gains. It also encourages churches to continue using the underpinnings of the Kairos Document as a weapon of justice in whatever oppressive circumstance may arise.Contribution: This article contributes to scholarship by drawing on the theological underpinnings of the Kairos Document to continue challenging churches to confront governments when they abuse their citizens for selfish gains.